Electrochemical Investigation of Iron-Catalyzed Atom Transfer Radical Polymerization - Gianluca Gazzola; Sebastiano Pasinato; Marco Fantin; Niccolò Braidi; Cristina Tubaro; Christian Durante; Abdirisak Ahmed Isse (Molecules, 2022)
Use of iron-based catalysts in atom transfer radical polymerization (ATRP) is very interesting because of the abundance of the metal and its biocompatibility. Although the mechanism of action is not well understood yet, iron halide salts are usually used as catalysts, often in the presence of nitrogen or phosphorous ligands (L). In this study, electrochemically mediated ATRP (eATRP) of methyl methacrylate (MMA) catalyzed by FeCl3, both in the absence and presence of additional ligands, was investigated in dimethylformamide. The electrochemical behavior of FeCl3 and FeCl3/L was deeply investigated showing the speciation of Fe(III) and Fe(II) and the role played by added ligands. It is shown that amine ligands form stable iron complexes, whereas phosphines act as reducing agents. eATRP of MMA catalyzed by FeCl3 was investigated in different conditions. In particular, the effects of temperature, catalyst concentration, catalyst-to-initiator ratio, halide ion excess and added ligands were investigated. In general, polymerization was moderately fast but difficult to control. Surprisingly, the best results were obtained with FeCl3 without any other ligand. Electrogenerated Fe(II) effectively activates the dormant chains but deactivation of the propagating radicals by Fe(III) species is less efficient, resulting in dispersity > 1.5, unless a high concentration of FeCl3 is used.